(3OdGFd GdEYLGRs - (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
(3hHYO aEfG EPG JUaMfG GdaVGFd dfYQa efGRdgG ai GdTQa hJHjf ehGbYgG ef GdYXe hJYde Gi efgG GMb HGdJbOje hGSHb ai GSJMHGH GdJYXje s
(3BNQgG (B:s
(3hfSFd Gddg JYGdi Cf jLYd cd eG ffTFg hfbUOg dhLgg NGdUkG hGdi QVGg YR hLd eDOjkG Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B606s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B759s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs